Association of Mycoplasma pneumoniae infection with Henoch-Schonlein purpura - Yiallouros, Panayiotis K.; Moustaki, Maria; Voutsioti, Aikaterini; Sharifi, Fariba; Karpathios, Themistocles (My University, 2013)
We present a child with Henoch-Schonlein purpura and Mycoplasma pneumoniae infection, an association that was rarely described in the literature. The infection was confirmed serologically and by using PCR.
Keywords: Henoch-Schonlein purpura; Mycoplasma pneumoniae; PCR